2012
DOI: 10.17925/ohr.2012.08.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiotherapy for Liver Metastases

Abstract: Liver metastases are common in oncologic patients, causing substantial morbidity and mortality. Systemic therapy is now standard palliative treatment for most patients with liver metastases, often providing transient responses and increased overall survival. In selected oligometastatic patients, local treatment can lead to long disease-free intervals and even permanent disease control. Although surgery remains the gold standard of local treatments, most patients will not be appropriate surgical candidates. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Stereotactic body radiotherapy is also a safer alternative to a metastasectomy, which carries surgical risks. 33 Stereotactic body RT is preferred over radiofrequency ablation or transcatheter arterial chemoembolization in patients who previously underwent Whipple procedure given the high risk of hepatic abscess formation. 34,35 Prospective studies have demonstrated that SBRT is a safe and effective treatment modality for LM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotactic body radiotherapy is also a safer alternative to a metastasectomy, which carries surgical risks. 33 Stereotactic body RT is preferred over radiofrequency ablation or transcatheter arterial chemoembolization in patients who previously underwent Whipple procedure given the high risk of hepatic abscess formation. 34,35 Prospective studies have demonstrated that SBRT is a safe and effective treatment modality for LM.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose ablative RT such as SBRT may be a therapeutic option for inoperable LM or patients who are not surgical candidates, which is the case in the majority of MPC patients. Stereotactic body radiotherapy is also a safer alternative to a metastasectomy, which carries surgical risks 33 . Stereotactic body RT is preferred over radiofrequency ablation or transcatheter arterial chemoembolization in patients who previously underwent Whipple procedure given the high risk of hepatic abscess formation 34,35 .…”
Section: Discussionmentioning
confidence: 99%